Development of a Water Temperature and pH Measurement System for Fish Ponds - Jaffar, Jasman (2009)
Breeding fish in the pond is one of the main sources of food to Malaysian. Water is an important medium for fish and other organisms which live in it. The aquaculture activities such as fish breeding in the pond depend on the suitable water quality. The water quality is one of the major factors in determining a good quality of fish and optimum earning. Fish Breeder needs some knowledge about water quality because the aquaculture activities will face high risk if the quality of water is out of the standard level. Water Temperature and pH Measurement System is vital in controlling the water quality so that the problem regarding the water quality can be detected early, if weather changes suddenly such as heavy rain or increased in whether temperature. This instrument also will help to ensure the produce of fish and the quality which are not affected due to the water quality factor. This research is aiming in developing a digital measurement device which can determine the water quality parameter in the pond. It also gives an early warning in avoiding the process to the fish growth in the pond. By using this instrument, fish breeder can detect the changes in water quality that influence the growth and the health of the fish. The digital measurement system is for monitoring the parameter of water quality for pH and temperature. This digital measurement can be applied at a location of the pond. It is portable equipment, cheap and reliable for water quality monitoring. This instrument was built using microcontroller AT89S52 with pH and temperature sensor together by Liquid Crystal Display (LCD) and keypad to be used easily. The programming language is used to write the program to determine the water quality parameter value which detected by the sensors and show the each parameter value at LCD then remind the fish breeder the situation of water quality in the pond. This measurement device is tested at Pusat Ternakan Ikan, Lembaga Kemajuan Pertanian Kemubu (KADA), KM 24 Ketereh, Kelantan and this testing was done at various ponds. This measurement device is very useful and easy to use without needs more technical knowlegde. The fish breeder can take immediate action if water quality parameter which been measured higher than the standard measurement.